ELECTRIFICATION IN THE UZBEKISTAN RAILWAYS SECTOR AND ITS ECONOMIC SIGNIFICANCE (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article discusses electrification work in the railway sector in the Republic of Uzbekistan and the reforms being implemented in this regard.
Keywords: Electrification of the sector, Uzbekistan Railways, electrification and energy, railway section, electricity supply, diesel fuel, foreign investment.